Ê gente que samba! práticas culturais e sociabilidades na cidade de Aracaju/SE - Santana, Cleber de Oliveira (2011)
The popular celebrations, specialy, the "sambas", in the city of Aracaju/SE are theme of investigation in this study, objectifying to evidence the cultural practices and the places where the population promoted their actions directed to the constitution of community bonds and festive meetings, identifying their ways of life and experiences, their habits and their inheritance, in a intense process of sociability, cultural exchanges/loans, analyzed from the social history and the culture, providing thereby possibilities on reading a past/present. Characterizing the place and map its context is indispensable in works that deal with entertainment of social strata, mainly with references, feelings and affective bonds/links with the place and their social dynamics inherited from african matrices. The period chosen includes the thirties of twentieth century, where we will see groups of work-people in consolidation in a city in the middle of organization of a becoming urbes